Hubungan Tingkat Pengetahuan Kepala Keluarga Dengan Perilaku Pencegahan Demam Berdarah Dengue Di Desa Sendangmulyo Kabupaten Blora - Ginandra, Imba Wahyu; , dr. Burhanudin Ichsan, M.Med,Ed.,M.Kes; , dr. Erika Diana Risanti (2015)
Introduction: Dengue Hemorrhagic Fever is a disease caused by a virus through the intermediary of mosquitoes that spread very quickly and is one example of a disease that can cause public health emergencies. Promotive and preventive efforts through improving the quality of the knowledge and behaviour of the patriarchs can be an alternative since the expensiveness of curative and rehabilitative efforts. The lack of knowledge and poor prevention behaviour can be a problem in the eradication of Dengue Hemorrhagic Fever. Objective: This research aimed to know the correlation between patriarchs' knowledge level and prevention behaviour of Dengue Hemorrhagic Fever. Method: The design of this research is an analytic observational with a crosssectional approach. The total of respondents is thirty six (36) patriarchs who are chosen by using cluster random sampling technique. The researcher uses Chisquare test by SPSS 21 to find out the correlation between patriarchs' knowledge level and prevention behaviour of Dengue Hemorrhagic Fever. Result: The total of patriarchs who have high level of knowledge is twenty-three patriarchs (63. 9 %) and those who have poor level of knowledge are thirteen patriarchs (36. 1 %). The statistical analysis shows the value of p is 0. 005. Conclusion: There is a significant correlation between patriarchs' knowledge level and the prevention behaviour of Dengue Hemorrhagic Fever in Sendangmulyo, Blora.